HOW INTERACTIVE DIGITAL COMMUNITIES IMPACT PUBLIC RELATIONS - JOAN TIRWYN HASSAN; EMMANUEL JIBB ADAMS; JOY AMARACHI OFORDI (International Studies Journal)
In the ever-changing landscape of communication, this study investigates the impact of interactive digital communities on public relations. By exploring the dynamic relationship between interactive media and PR in the digital age, the paper examines the multifaceted influence of interactive media in transforming contemporary public relations practices within the modern digital realm. Specifically, the paper explores both the opportunities and challenges pose by interactive media outlets and their profound effects and impacts on the practice of public relations. Guided by the framework of Theory of Interactive Media Effects, the paper argues how advancement in interactive media platforms, using Public Relations as communicative tool, drives societal changes.  It concludes by advocating for Public Relations professionals to adapt strategies that effectively harness the potential of interactive media, recognizing its dyadic nature viz-a-viz its numerous opportunities and challenges for effective communication.  Emphasis is further laid on the crucial role of interactive media in shaping the daily activities and communicative functions of Public Relations practitioners, underscoring the importance of aligning Public Relations strategies with the dynamism of digital interactive platforms.